A Longitudinal Perspective on the Impact of Immune Status on the HIV-1 Latent Reservoir and Neurocognitive Outcomes in Virologically Suppressed Children - Naidoo, Shalena (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.